2018
DOI: 10.5194/acp-18-13813-2018
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the formation and composition of secondary organic aerosol from diesel exhaust using parameterized and semi-explicit chemistry and thermodynamic models

Abstract: Abstract. Laboratory-based studies have shown that combustion sources emit volatile organic compounds that can be photooxidized in the atmosphere to form secondary organic aerosol (SOA). In some cases, this SOA can exceed direct emissions of primary organic aerosol (POA). Jathar et al. (2017a) recently reported on experiments that used an oxidation flow reactor (OFR) to measure the photochemical production of SOA from a diesel engine operated at two different engine loads (idle, load), two fuel types (diesel, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
43
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(43 citation statements)
references
References 72 publications
0
43
0
Order By: Relevance
“…In the high-NO x experiments, inorganic nitrate and ON were formed, with both of them generating NO + and NO + 2 fragments. Hence the inorganic and organic nitrate must be distinguished from each other, and the total N signal was determined by following the approach proposed by Farmer et al (2010;see Supplement). Ground-based observations: time series (a-d) and wind rose plots (e-i) of gas-phase species (SO 2 and NO x ), particle-phase species (organics, SO 4 , NO 3 , NH 4 and rBC) and PMF factors (HOA, LO-OOA and MO-OOA).…”
Section: Laboratory Flow Tube Experimentsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the high-NO x experiments, inorganic nitrate and ON were formed, with both of them generating NO + and NO + 2 fragments. Hence the inorganic and organic nitrate must be distinguished from each other, and the total N signal was determined by following the approach proposed by Farmer et al (2010;see Supplement). Ground-based observations: time series (a-d) and wind rose plots (e-i) of gas-phase species (SO 2 and NO x ), particle-phase species (organics, SO 4 , NO 3 , NH 4 and rBC) and PMF factors (HOA, LO-OOA and MO-OOA).…”
Section: Laboratory Flow Tube Experimentsmentioning
confidence: 99%
“…Extensive field investigations have demonstrated the significant formation of pON via nocturnal NO 3 radical chemistry of biogenic VOCs on a global scale (Kiendler-Scharr et al, 2016;Ng et al, 2017). Daytime production of pON has also been observed in urban and forested regions (Farmer et al, 2010;Kiendler-Scharr et al, 2016;Lee et al, 2016), but the potential role of anthropogenic VOCs in pON formation remains largely unexplored. Recently, a field study demonstrated that oil and natural gas drilling operations were associated with alkanederived pON production (L. .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…SOA production (Eluri et al, 2017) and global SOA budgets (Hodzic et al, 2016). Our findings highlight the important role of daytime pON formation for SOA production in urban and industrial regions with strong emissions of anthropogenic IVOCs and NOx (e.g.…”
Section: Introductionmentioning
confidence: 64%
“…Zhao et al, 2015). Including IVOCs in SOA prediction models can have great impact on estimating the production of anthropogenic SOA in urban environments and global SOA budgets (Eluri et al, 2017;Hodzic et al, 2016). However, anthropogenic pON formation chemistry has not been fully integrated into current SOA prediction models.…”
mentioning
confidence: 99%